Preliminary assessment of surface pressure measurements on a metallic, additive manufactured wind tunnel model. Issue 201 (June 2020) - McCarthy, J.; Teske, T.; Lam, S.; Jones, M.
Abstract: Producing metallic wind-tunnel models with integrated pressure taps (i.e. taps formed during the manufacture process) via additive manufacturing (AM) techniques could present several advantages over conventionally manufacturing (CM) pressure-tapped models. However, there are limited reports of AM wind-tunnel models in general. This study describes, in brief, the design and manufacture of a metallic hemispherical wind-tunnel model with integrated pressure taps, produced by Selective Laser Melting (SLM). Mean and unsteady pressure distributions are acquired as a preliminary performance metric for the AM model. The measurements generally agree with previously published results for hemisphere flows at similar experimental conditions; but discrepancies, thought to arise from the model surface finish rather than the SLM process, are evident in the span-wise pressure distributions. Nevertheless, the results are encouraging and extend the bounds of possibility in the use of AM techniques for wind-tunnel model production. Highlights: A metallic, pressure-tapped hemispherical wind tunnel model was made via additive manufacturing (AM). Measured pressure distributions on the AM hemisphere agree well with published data. It is clear that particular attention needs to be given to the AM model design. This study demonstrates an extension of AM techniques to cost-effective wind-tunnel model development.